Effect of incomplete reperfusion patterns on clinical outcome: insights from the ESCAPE-NA1 trial - Cimflova, Petra; Singh, Nishita; Kappelhof, Manon; Ospel, Johanna M; Sehgal, Arshia; Kashani, Nima; Almekhlafi, Mohammed A; Demchuk, Andrew M; Berrouschot, Joerg; Dorn, Franziska; Kelly, Michael E; Buck, Brian H; et al. (Journal of neurointerventional surgery, 2024)
BACKGROUND: Incomplete reperfusion (IR) after mechanical thrombectomy (MT) can be a consequence of residual occlusion, no-reflow phenomenon, or collateral counterpressure. Data on the impact of these phenomena on clinical outcome are limited. METHODS: Patients from the ESCAPE-NA1 trial with IR (expanded Thrombolysis In Cerebral Infarction (eTICI) 2b) were compared with those with complete or near-complete reperfusion (eTICI 2c-3) on the final angiography run. Final runs were assessed for (a) an MT-accessible occlusion, or (b) a non-MT-accessible occlusion pattern. The primary clinical outcome was modified Rankin Scale (mRS) 0-2 at 90 days. Our imaging outcome was infarction in IR territory on follow-up imaging. Unadjusted and adjusted incidence rate ratios (aIRR) with 95% confidence intervals (95% CI) were obtained. RESULTS: Of 1105 patients, 443 (40.1%) with IR and 506 (46.1%) with complete or near-complete reperfusion were included. An MT-accessible occlusion was identified in 147/443 patients (33.2%) and a non-MT-accessible occlusion in 296/443 (66.8%). As compared with patients with near-complete/complete reperfusion, patients with IR had significantly lower chances of achieving mRS 0-2 at 90 days (aIRR 0.82, 95% CI 0.74 to 0.91). Rates of mRS 0-2 were lower in the MT-accessible occlusion group as compared with the non-MT-accessible occlusion pattern group (aIRR 0.71, 95% CI 0.60 to 0.83, and aIRR 0.89, 95% CI 0.81 to 0.98, respectively). More patients with MT-accessible occlusion patterns developed infarcts in the non-reperfused territory as compared with patients with non-MT occlusion patterns (68.7% vs 46.3%). CONCLUSION: IR was associated with worse clinical outcomes than near-complete/complete reperfusion. Two-thirds of our patients with IR had non-MT-accessible occlusion patterns which were associated with better clinical and imaging outcomes compared with those with MT-accessible occlusion patterns.
Keywords: senioři; Thrombectomy; Stroke; reperfuze; výsledek terapie; Middle Aged; mužské pohlaví; Prospective Studies; trombektomie; ženské pohlaví; Angiography; Humans; prospektivní studie; lidé středního věku; Cerebral Infarction; Female; Aged; cerebrální infarkt; Reperfusion; Treatment Outcome; lidé; Male